Snow- and ice-ecosystem cleaning capability of the pucciniomycotinous yeast Phenoliferia psychrophenolica - Jade A. Ezzedine; Pierre Guenzi-Tiberi; Gaëlle Villain; Riccardo Aiese Cigliano; Yacine Diagne; Enzo Franceschi; Elodie Drula; Jérôme Forêt; Jean-Gabriel Valay; Lenka Procházková; Daniel Remias; Nicolas Terrapon; et al. (Communications Biology)
Abstract Psychrophilic pucciniomycotinous yeasts inhabit snowfields and glacial ecosystems worldwide, yet their ecological role remains unclear. We isolated a clonal strain of Phenoliferia psychrophenolica (LCC-F-001-001) from an alpine red snowfield. Its 42-Mbp genome contains 11,523 genes, including 37 ice-binding protein genes, the highest number recorded in fungi, mainly acquired through horizontal transfers. This yeast tolerates freezing, grows optimally at 10 °C and forms pseudohyphae above 15 °C. Known to assimilate phenol and small metabolites, we found LCC-F-001-001 also hydrolyzes carotenoid and phenolic pigments from snow and glacier ice algae. LCC-F-001-001 genome encodes ~ 500 carbohydrate-active enzymes, ranking among the most catalytically versatile sequenced Microbotryomycetes, alongside a related permafrost species. P. psychrophenolica and related fungi are therefore key players in snow and ice ecosystems, capable of degrading organic molecules in snowfields and glaciers, likely during algal bloom declines, and connecting the carbon cycle between cryospheric environments and soils through their exceptional metabolic adaptability.